Evaluation and Implementation Registration of Outpatient with Online Systems at Health Services Center - Imania Halwa El Kariema; Sandu Siyoto; Ratna Wardani (Journal for Quality in Public Health, 2021)
In an effort to improve the health status of the Indonesian people, the quality of hospital services must always be improved through easy access to health facilities. One way is to use an online-based registration service system. This literature review aims to examine some of the problems that occur in online-based registration services. The method used is by conducting a review of various journals on international and online-based registration services in Indonesia, in the 2010-2019 period. Searching for journals using ResearchGate and Google Scholar, the journals that are looking for are journals in the health sector, after several screenings and reviews that match the theme, 22 journals are obtained. The use of an online-based registration service system can reduce the length of patient queues when registering before getting service from a doctor. Several hospitals in Indonesia have used online-based registration services, but there are still many obstacles. This obstacle can occur during the planning process as well as during the service implementation process, for example, namely lack of human resources, missing SOPs, a patient who cannot use a cellphone and a lack of information on patients about the online registration system. The benefits of making this literature review are expected that hospitals that will implement online-based registration services understand and understand what are the factors of obstacles to online registration services so that they are better prepared to avoid these obstacle factors.